The Effect of Prudence and Financial Distress on Tax Avoidance with Independent Commissioners as A Moderation Variable - Hulki, Husnul; Darmayanti, Yeasy (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the influence of prudence and financial distress against tax avoidance with an independent commissioner as a moderation variable. This study uses quantitative analysis by utilizing secondary data from multinational companies listed on the Indonesia Stock Exchange (IDX) in the 2019–2023 period. Sample selection is carried out by technique purposive sampling So that 22 companies were obtained as research samples. The data analysis method used is Moderated Regression Analysis (MRA), with hypothesis testing assisted using IBM SPSS software version 27. The results of the study indicate that: (1) prudence affects tax avoidance; (2) financial distress has no effect on tax avoidance; (3) the independent commissioner is unable to moderate the relationship between the prudence and tax avoidance; and (4) the independent commissioner is unable to moderate the relationship between the financial distress and tax avoidance.